Higher TIGIT+ γδ TCM cells may predict poor prognosis in younger adult patients with non-acute promyelocytic AML - Hou, Qi; Wang, Penglin; Kong, Xueting; Chen, Junjie; Yao, Chao; Luo, Xiaodan; Li, Yangqiu; Jin, Zhenyi; Wu, Xiuli (Frontiers in Immunology, 2024)
γδ T cells recognize and exert cytotoxicity against tumor cells. They are also considered potential immune cells for immunotherapy. Our previous study revealed that the altered expression of immune-checkpoint T-cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) on γδ T cells may result in immunosuppression and is possibly associated with a poor overall survival in acute myeloid leukemia (AML). However, whether γδ T cell memory subsets are predominantly involved and whether they have relationship with clinical outcomes in AML patients under the age of 65 remain unclear. In this study, we developed a multicolor flow cytometry-based assay to monitor the frequency and distribution of γδ T cell subsets, including central memory γδ T cells (TCM γδ), effector memory γδ T cells (TEM γδ), and TEM expressing CD45RA (TEMRA γδ), in peripheral blood from 30 young (≤65 years old) newly diagnosed non-acute promyelocytic leukemia (also known as M3) AML patients (AMLy-DN); 14 young patients in complete remission (AMLy-CR); and 30 healthy individuals (HIs). Compared with HIs, AMLy-DN patients exhibited a significantly higher differentiation of γδ T cells, which was characterized by decreased TCM γδ cells and increased TEMRA γδ cells. A generally higher TIGIT expression was observed in γδ T cells and relative subsets in AMLy-DN patients, which was partially recovered in AMLy-CR patients. Furthermore, 17 paired bone marrow from AMLy-DN contained higher percentages of γδ and TIGIT+ γδ T cells and a lower percentage of TCM γδ T cells. Multivariate logistic regression analyses revealed the association of high percentage of TIGIT+ TCM γδ T cells with an increased risk of poor induction chemotherapy response. In conclusion, we investigated the distribution of γδ T cells and their memory subsets in non-M3 AML patients and suggested TIGIT+ TCM γδ T cells as potential predictive markers of induction chemotherapy response.